The vegetative status and bioelectric activity of the brain in different terms of the remote period of a fighting craniocereberal trauma - Ye. V. Osintseva; M. V. Nadezhdina; M. N. Zhezher; O. S. Kurus; N. I. Skulskaya (Бюллетень сибирской медицины, 2010)
2 groups on 35 patients from 32 till 52 years which have transferred an easy fighting craniocerebral trauma. It is spent electroencephalographic (EEG) research, the computer analysis with definition of indexes of the basic rhythms, the vegetative status under the program of variability of a rhythm of heart is studied, functional classes (FC) on D.I. Zhemajtite are defined. At all patients changed types EEG prevailed. It is noted low FC at patients with I, II, V types ЭЭГ. Correlation of type EEG with level FC is revealed: at patients with V type EEG prevailed IV and V, with I and II types EEG — higher (II, III) FC. The high index of an alpha rhythm correlates with high II FC, and a beta rhythm with III FC. Decrease in adaptable mechanisms of vegetative regulation defines necessity of medicament correction.